MIGRANT CRISIS: OPEN DOOR POLICY ANALYSIS - Stivani Ismawira Sinambela (Jurnal PIR : Power in International Relations, 2018)
This paper aims to explain migrant crisis that happen in Germany because Open Door Policy implemented by Germany under governmental Chancellor Angela Merkel in 2015. Since, Germany has issued various policies that serve as protection regime in dealing with migrant. In its application, it is ineffective until cause in significant and different impacts in every aspect since. Implementation of Open Door Policy to deal with the migrant crisis that occurred at Europe, a new hope in Germany to boost Germany's positive image. The conclusions obtained in the analysis of this study that some Germans hope this positive image will help remove some stains in the past against Germany reputation. Germany has become home to migrants where Germany once made hundreds of thousands of people migrants. Germany appears to have drastically curtailed its open-door policy for migrants. therefore Open-door policy has resulted in the disintegration of countries in the EU region. There are four risks that will be experienced by the European Union, namely the north-south divide on migrants by rethinking and suspension of the agreement called the Schengen system. This study uses literature study as a method and in the data analysis uses descriptive qualitative.